THE IMPLEMENTATION OF THE NUMBERED-HEAD-TOGETHER METHOD TO IMPROVE ELEMENTARY SCHOOL STUDENTS’ LEARNING PROCESS - Ahmad Fauzan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of Class IV students’ learning process at SDN Segeran Kidul Indramayu by applying the Numbered-Head-Together cooperative learning model. The method used is classroom action research (CAR) using the Kemmis and Mc. Taggart model for three cycles. The research instruments include student and teacher observation sheets, multiple-choice questions, and documentation. Data analysis includes data collection, data reduction, data presentation, and conclusion. The results of the research imply that there was an improved learning process followed by significant learning outcomes. There was an increased percentage of students’ learning process at 51% in the first cycle. The increased percentage of students’ learning process in the second cycle was 69.38% with a significant percentage of 18.38% from the first cycle. In the third cycle, students fulfilled the learning process indicator of 84.5% with a significant percentage of 15.12% from the second cycle. This significant percentage was reinforced by the pre-test average score of 46.73 smaller than the post-test average score of 62.82 with a completeness percentage of 21.73% in the first cycle. The percentage of students’ learning outcomes in the second cycle was 47.82% with an average value of 72.17. The increased percentage was 26.09% based on the student’s learning outcomes in the first cycle. The percentage of students’ learning outcomes in the third cycle was 82.60% with an average value of 82.39. There was a significant percentage of 34.78% based on the student’s learning outcomes in the second cycle. These results have achieved the school’s minimum criteria of mastery learning indicator (KKM) at 75%. Therefore, the Numbered-Head-Together method is effective and able to increase the elementary school students’ learning process, especially at SDN Segeran Kidul Indramayu.